Effect of rhPDGF-BB on bone turnover during periodontal repair - David P. Sarment (Blackwell Synergy, 2006)
Purpose: Growth factors such as platelet-derived growth factor (PDGF) exert potent effects on wound healing including the regeneration of periodontia. Pyridinoline crosslinked carboxyterminal telopeptide of type I collagen (ICTP) is a well-known biomarker of bone turnover, and as such is a potential indicator of osseous metabolic activity. The objective of this study was to evaluate the release of the ICTP into the periodontal wound fluid (WF) following periodontal reconstructive surgery using local delivery of highly purified recombinant human PDGF (rhPDGF)-BB. Methods: Forty-seven human subjects at five treatment centres possessing chronic severe periodontal disease were monitored longitudinally for 24 weeks following PDGF regenerative surgical treatment. Severe periodontal osseous defects were divided into one of three groups and treated at the time of surgery with either: btricalcium phosphate (TCP) osteoconductive scaffold alone (active control), b- TCP10.3 mg/ml of rhPDGF-BB, or b-TCP11.0 mg/ml of rhPDGF-BB. WF was harvested and analysed for local ICTP levels by radioimmunoassay. Statistical analysis was performed using analysis of variance and an area under the curve analysis (AUC). Results: The 0.3 and 1.0 mg/ml PDGF-BB treatment groups demonstrated increases in the amount of ICTP released locally for up to 6 weeks. There were statistically significant differences at the week 6 time point between b-TCP carrier alone group versus 0.3 mg/ml PDGF-BB group (po0.05) and between b-TCP alone versus the 1.0 mg/ml PDGF-BB-treated lesions (po0.03). The AUC analysis revealed no statistical differences amongst groups. Conclusion: This study corroborates the release of ICTP as a measure of active bone turnover following local delivery of PDGF-BB to periodontal osseous defects. The amount of ICTP released from the WF revealed an early increase for all treatment groups. Data from this study suggests that when PDGF-BB is delivered to promote periodontal tissue engineering of tooth-supporting osseous defects, there is a direct effect on ICTP released from the wound.